Fulminant Giant Cell Myocarditis vs. Lymphocytic Myocarditis: A Comparison of Their Clinical Characteristics, Treatments, and Outcomes - Hu, Yuxiao; Ren, Jie; Dong, Xueqi; Zhang, Di; Qu, Yi; Yang, Chunxue; Sun, Yang; Li, Jinghui; Luo, Fang; Wang, Wei; Wang, Huanhuan; Qing, Ping; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Fulminant myocarditis (FM) is a rapidly progressive and frequently fatal form of myocarditis that has been difficult to classify. This study aims to compare the clinical characteristics, treatments and outcomes in patients with fulminant giant cell myocarditis (FGCM) and fulminant lymphocytic myocarditis (FLM). Methods and results: In our retrospective study, 9 patients with FGCM (mean age 47.9±7.5 years, 6 female) and 7 FLM (mean age 42.1±12.3 years, 4 female) patients confirmed by histology in the last 11 years were included. Most patients with FGCM and FLM were NYHA functional class IV (56% vs. 100%, p = 0.132). Patients with FGCM had significantly lower levels of high-sensitivity C-reactive protein [hs-CRP, 4.4 (2.0-10.2) mg/L vs. 13.6 (12.6-14.6) mg/L, P = 0.004, data shown as the median with IQR], creatine kinase-myoglobin [CK-MB, 1.4 (1.0-3.2) ng/ml vs. 14.6 (3.0-64.9) ng/ml, P = 0.025, median with IQR], and alanine aminotransferase [ALT, 38.0 (25.0-61.5) IU/L vs. 997.0 (50.0-3080.0) IU/L, P = 0.030, median with IQR] and greater right ventricular end-diastolic diameter (RVEDD) [2.9±0.3 cm vs. 2.4±0.6 cm, P = 0.034, mean ± SD] than those with FLM. No differences were observed in the use of intra-aortic balloon pump (44% vs. 43%, p = 1.000) and extracorporeal membrane oxygenation (11% vs. 43%, p = 0.262) between the two groups. The long-term survival rate was significantly lower in FGCM group compared with FLM group (0% vs. 71.4%, p = 0.022). A multivariate cox regression analysis showed the level of hs-CRP (hazard ratio = 0.871, 95% confidence interval: 0.761~0.996, P = 0.043) was an independent prognostic factor for FM patients. Furthermore, the level of hs-CRP had a good ability to discriminate between patients with FGCM and FLM (AUC = 0.94, 95% confidence interval: 0.4213~0.9964). Conclusions: The inflammatory response and myocardial damage in the patients with FGCM was milder than those with FLM. Patients with FGCM had a distinctly poorer prognosis compared with those with FLM. Our results suggest that hs-CRP could be a promising prognostic biomarker and a hs-CRP level of 11.71 mg/L is an appropriate cutoff point for the differentiating diagnosis between patients with FGCM and FLM.